2008
DOI: 10.1200/jco.2007.14.5482
|View full text |Cite|
|
Sign up to set email alerts
|

Dose- and Schedule-Dependent Inhibition of the Mammalian Target of Rapamycin Pathway With Everolimus: A Phase I Tumor Pharmacodynamic Study in Patients With Advanced Solid Tumors

Abstract: Everolimus achieved mTOR signaling inhibition at doses below the DLT. A dosage of 10 mg/d or 50 mg/wk is recommended for further development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
366
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 501 publications
(397 citation statements)
references
References 46 publications
28
366
2
1
Order By: Relevance
“…Both everolimus and LY294002 acted mainly by induction of cell-cycle arrest, particularly in G 1 phase, which was similar with other study using PI3K and mTOR dual inhibitors (17). Target mTOR therapy alone can cause a multiple feedback loops and cross-talk with other signaling pathways, which may lead to pAkt activation and attenuate the responses to mTOR inhibition (14). Here, everolimus alone or combination with tamoxifen treatment can inhibit mTOR activity, but pAkt expression was upregulated in ER-positive breast cancer cell lines and in vivo tumor model, which may explain the relative low response rate in metastatic breast cancer therapy (11).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Both everolimus and LY294002 acted mainly by induction of cell-cycle arrest, particularly in G 1 phase, which was similar with other study using PI3K and mTOR dual inhibitors (17). Target mTOR therapy alone can cause a multiple feedback loops and cross-talk with other signaling pathways, which may lead to pAkt activation and attenuate the responses to mTOR inhibition (14). Here, everolimus alone or combination with tamoxifen treatment can inhibit mTOR activity, but pAkt expression was upregulated in ER-positive breast cancer cell lines and in vivo tumor model, which may explain the relative low response rate in metastatic breast cancer therapy (11).…”
Section: Discussionsupporting
confidence: 71%
“…Baselga and colleagues showed that pAkt expression was upregulated in 50% of solid tumors treated with everolimus alone in a phase I study, which may attenuate the response with mTOR inhibitor (14). Among all the upstream signaling pathways in the mTOR complex, PI3K pathway is the most relevant in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…1B). The differential response of these lines was consistently maintained across a range of everolimus concentrations, including the clinically relevant concentration of 50 n m (Tabernero et al ., 2008). No difference in everolimus response and the anatomical location along the biliary tract from which the cell lines originated was observed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In both cases, rapamycin relieves feedback inhibition and promotes PI3K -AKT survival signaling. The clinical relevance of losing feedback inhibition is emphasized in human trials that find rapamycin increases AKT activation in many malignancies (O'Reilly et al 2006;Tabernero et al 2008;Sudarsanam and Johnson 2010). Rapamycin can also activate the MAPK pathway, providing another potential avenue to resistance (Carracedo et al 2008).…”
Section: Mtor and Cell Survivalmentioning
confidence: 99%